A Gallant Grenadier: A Tale of the Crimean War - Brereton, F. S. (Frederick Sadleir), 1872-1957; Paget, Walter, 1863-1935 (Salt Lake City, UT : Project Gutenberg, 2010)
"A Gallant Grenadier: A Tale of the Crimean War" by F. S. Brereton is a historical novel likely written in the late 19th century. The story revolves around Philip Western, an adopted boy raised by a strict vicar who hopes to mold him into a clergyman, but finds instead a spirited and mischievous lad full of life and adventure. As Philip navigates the expectations of his guardians against his own desire for freedom, the narrative sets the stage for his eventual enlistment, hinting at themes of rebellion, identity, and the call for a more adventurous life. The opening of the book introduces us to Philip Western and his adoptive father, Edward Western, who is frustrated by Philip's mischievous behavior, particularly a prank involving the mayor and a booby trap. Despite his father's sternness, the contrast between Edward$1 (Bs serious demeanor and the lightheartedness of Philip's spirit is clear, with Edward's brother-in-law, Joe Sweetman, providing comic relief and supporting Philip's lively nature. We see Philip's dilemmas unfold as he navigates strict standards at home and the contrasting freedom he experiences at school. The narrative hints at Philip's struggle against the confines of his upbringing and foreshadows his eventual decision to seek a life beyond the expectations imposed on him, setting the scene for his future endeavors, including his exploration into military life. (This is an automatically generated summary.)s
Release date is 2010-06-20
Produced by Nick Hodson of London, England
Keywords: Crimean War, 1853-1856 -- Juvenile fiction